Implementation of marketing strategies of Saint Louis College Libraries - Lim, Joane O. (Saint Louis College, City of San Fernando, La Union : [s.n.], 2022)
This study is a quantitative research that assessed the implementation of the marketing strategies of Saint Louis College Libraries' in the following areas: library orientation, list of newly processed library materials, book display, bulletin boards, E-mail, E-resources, Social media, and SLC Web OPAC. Specifically, the study looked into the respondents' level of library satisfaction with the marketing strategies of SLC libraries in the following areas: Timeliness, Ease of Access, Staff, Sufficiency and Suitability. In this study, the descriptive research designed was used. College Faculty, BEDS (Basic Education School) Faculty, SAS (School of Advanced Studies) Students, College Students and BEdS Students of Saint Louis College were among the respondents. The overall population is 6,710 in the first semester of SY 2020-2021, with the sample size is 377. The study made use of survey questionnaire in Google format as the main tool in gathering the needed data. The statistical method utilized was the weighted mean. The survey revealed that implementation of the existing marketing strategies of Saint Louis College were highly implemented. The respondents' were moderately satisfied. On the other hand, BEdS students were moderately implemented on the existing marketing strategies and satisfied on the level of satisfaction of marketing strategies. Based on the conclusions, most of the respondents were very much aware and well educated about the existing library marketing strategies and their needs are being met. On the other hand, there is room for improvement on the BEdS students. It was highly recommended that the enhanced marketing programs for the SLC library should be adopted and implemented to continuously assess and improve the library services and resources of the SLC library.
References: pages 89-101.
CHED-La Union
Keywords: Academic libraries -- Administration